Affectivity as stance: multimodal stance-taking in audiovisual documentations of Polish and German parliamentary debates - Cornelia Müller; Maciej Karpiński; Clara Kindler-Mathôt; Katarzyna Klessa; Ewa Jarmołowicz-Nowikow; Jana Katharina Junge; Katerina Papadopoulou; Brygida Sawicka-Stępińska (Frontiers in Psychology)
This paper presents a media-aesthetic framework to study affectivity as a stance. This framework opens up a new perspective on multimodal affective stance-taking in the context of specific media ecologies. It exemplifies this new approach with case studies of the official audiovisual documentation of political debates in the German Bundestag and the Polish Sejm. This new approach addresses the intertwining of audiovisual multimodality with verbo-gestural expressivity (or the multimodality of speaking). Adopting a phenomenological position, we are interested in how the orchestration of the debates as audiovisual events moves the spectators. The concepts ‘Expressive Movement’ and ‘Dynamic Forms of Vitality’ serve as theoretical and methodological references to capture the affective dynamics of audiovisual debates and how these audiovisual images modulate the perceptions and experiences of the spectators. To illustrate and substantiate this approach for linguistic and media analyses of affective stance-taking, the paper outlines basic assumptions and methods. It offers two exemplary case studies from German and Polish parliamentary debates. It is concluded that bringing together media-aesthetic with linguistic analyses of multimodal communication and interaction provides not only a valid starting point for future research of multimodal stance-taking in different media ecologies but also allows researchers to address how and why spectators of audiovisual media performances are moved affectively.